2011
DOI: 10.1080/0951192x.2011.602362
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy ART K-Means Clustering Technique: a hybrid neural network approach to cellularmanufacturing systems

Abstract: Cellular manufacturing system (CMS) is regarded as an efficient production strategy for batch type of production. Literature suggests, since the last two decades neural network has been intensively used in cell formation while production factor such as operation time is merely considered. This paper presents a new hybrid neural network approach, Fuzzy ART K-Means Clustering Technique (FAKMCT), to solve the part machine grouping problem in CMS considering operation time. The performance of the proposed techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This method clearly outperforms the K-means method which is a standing cell formation technique and used heavily in past literatures. 3,13,58 MCDT model is also slightly quicker than the K-means method in terms of CPU time. A graphical analysis on the performance of the proposed approach and the improvement in terms of CPU time is presented in Figure 12.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This method clearly outperforms the K-means method which is a standing cell formation technique and used heavily in past literatures. 3,13,58 MCDT model is also slightly quicker than the K-means method in terms of CPU time. A graphical analysis on the performance of the proposed approach and the improvement in terms of CPU time is presented in Figure 12.…”
Section: Resultsmentioning
confidence: 97%
“…These are processing time, processing sequence, machine utilization, production volume, available machining hours, machine breakdown time and many more. 13 Yet researchers are working with 0–1 CFP till present time, which is merely significant in practice at present. 14 The usage of ordinal data is being intensified in latest research of CMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUs take one or more input values, combine them into a single value using propagation rule, then transform them into an output value through an activation/transfer function. Complex networks can be constructed by connecting a number of PUs together (Sengupta et al, 2011). The simplest network is a group of PUs arranged in a single layer.…”
Section: Overview Of Annmentioning
confidence: 99%
“…The proposed SOM approach produced solutions with a grouping efficacy that is at least as good as any results earlier reported in the literature and improved the grouping efficacy for 70%. Sengupta et al (2011) demonstrated a new hybrid neural network approach, fuzzy ART K-means clustering technique (FAKMCT), to solve the PMG problem considering operation time. The performance of the proposed technique is compared to the existing clustering models such as simple K-means algorithm and modified ART1 algorithm as found in the recent literature.…”
Section: Ann In Gt/cm: From 2001 To 2012mentioning
confidence: 99%